The politics of swidden farming, environment and development in eastern India - Das, Debojyoti (Anthem Press, an imprint of Wimbledon Publishing Company, 2018)
'The Politics of Swidden farming' is an ethnography of swidden farming practised - a characteristically remote, inaccessible and under-researched region of South Asia. The research ties on both archival-historical and contemporary ethnographic discourses on swidden farming and agrarian development among the eastern Naga community inhabiting the northeastern borderland state of Nagaland.